2004
DOI: 10.1093/aje/kwh141
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Consent in Epidemiologic Research: Evidence from Over 25,000 Responders

Abstract: Ethical guidelines in the United Kingdom require written consent from participants in epidemiologic studies for follow-up or review of medical records. This may cause bias in samples used for follow-up or medical record review. The authors analyzed data from seven general population surveys conducted in the United Kingdom (1996-2002), to which over 25,000 people responded. Associations of age, gender, and symptom under investigation with consent to follow-up and consent to review of medical records were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
175
5
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(199 citation statements)
references
References 18 publications
16
175
5
3
Order By: Relevance
“…We found the highest consent rate in the 16-24 age range, with little difference across the rest of the age spectrum, and although the association between age and consent in other studies has been inconsistent [38], this may reflect a greater willingness to share information secondary to greater exposure to and use of social media among this age group. The study also confirms the positive association between poorer health and consent to record linkage [14,30], which may arise because individuals with poor health, who are utilising the health service, can readily appreciate the benefits of linkage or want to give something back to the service.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…We found the highest consent rate in the 16-24 age range, with little difference across the rest of the age spectrum, and although the association between age and consent in other studies has been inconsistent [38], this may reflect a greater willingness to share information secondary to greater exposure to and use of social media among this age group. The study also confirms the positive association between poorer health and consent to record linkage [14,30], which may arise because individuals with poor health, who are utilising the health service, can readily appreciate the benefits of linkage or want to give something back to the service.…”
Section: Discussionsupporting
confidence: 66%
“…Participation bias has been reasonably well characterised, and studies have demonstrated that respondents participating in surveys are more likely to be female [14]; be of higher socioeconomic status and employed [15][16][17]; and to be educated [18] and married [15,18]. Some authors have found higher participation in older age groups whilst others did not (see [19] for review).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations